Determination of electron‐hole pair creation energy in Cd0.9Zn0.1Te0.98Se0.02 quaternary semiconductor for room‐temperature gamma‐ray detection - Sandeep K. Chaudhuri; Ritwik Nag; Utpal N. Roy; Ralph B. James; Krishna C. Mandal (Electronics Letters, 2024)
Abstract We report the first‐time measurement of the electron‐hole pair (ehp) creation energy (Wehp) in novel Cd0.9Zn0.1Te0.98Se0.02 (CZTS) quaternary semiconductor. CZTS in single crystalline form is poised to be the future of large‐volume room‐temperature gamma‐ray detectors due to its excellent compositional homogeneity with highly reduced defects, high‐Z (atomic number) constituents, wide bandgap (1.6 eV), and superior charge transport properties. Despite a great deal of study of the material and device properties since its inception, the Wehp in CZTS has not been measured experimentally. Accurate determination of Wehp is essential for calibration of the spectrometer and other theoretical calculations. In this study we have used an absolute calibration approach, which is based on an iterative approach that yields the Wehp as the best‐fit parameter. Using a 241Am alpha emitting radioisotope and a planar CZTS detector, the Wehp in CZTS was calculated to be 4.47 eV. The obtained value has been validated by accurately predicting the peak energy for gamma rays emitted by a 137Cs source and read by a CZTS detector with different dimensions. The dependences of the calculated Wehp value on the detector dimensions, type of interaction, and effect of charge trapping are also discussed.